2017
DOI: 10.3390/ijms18091900
|View full text |Cite
|
Sign up to set email alerts
|

Sample Size Estimation for Detection of Splicing Events in Transcriptome Sequencing Data

Abstract: Merging data from multiple samples is required to detect low expressed transcripts or splicing events that might be present only in a subset of samples. However, the exact number of required replicates enabling the detection of such rare events often remains a mystery but can be approached through probability theory. Here, we describe a probabilistic model, relating the number of observed events in a batch of samples with observation probabilities. Therein, samples appear as a heterogeneous collection of event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…We then confirmed the pluripotency of generated CRISPRa iPSC lines. Principal-component analysis (PCA) of bulk RNA-seq of 15 CRISPRa iPSC lines from 5 LCL and 2 fibroblast donors demonstrated that all CRISPRa iPSC lines grouped with previously published iPSC lines generated from blood and fibroblast cells using conventional methods ( Carcamo-Orive et al., 2017 ; Kilpinen et al., 2017 ) and distinct from LCL and fibroblasts ( Kaisers et al., 2017 ; Ozgyin et al., 2019 ) ( Figure 1 C). CRISPRa iPSC lines were then compared more closely with a total of 661 Human Induced Pluripotent Stem Cells Initiative (HipSci) iPSC lines, which showed that our cell lines grouped closely together with the HipSci lines ( Kilpinen et al., 2017 ) ( Figure 1 D).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…We then confirmed the pluripotency of generated CRISPRa iPSC lines. Principal-component analysis (PCA) of bulk RNA-seq of 15 CRISPRa iPSC lines from 5 LCL and 2 fibroblast donors demonstrated that all CRISPRa iPSC lines grouped with previously published iPSC lines generated from blood and fibroblast cells using conventional methods ( Carcamo-Orive et al., 2017 ; Kilpinen et al., 2017 ) and distinct from LCL and fibroblasts ( Kaisers et al., 2017 ; Ozgyin et al., 2019 ) ( Figure 1 C). CRISPRa iPSC lines were then compared more closely with a total of 661 Human Induced Pluripotent Stem Cells Initiative (HipSci) iPSC lines, which showed that our cell lines grouped closely together with the HipSci lines ( Kilpinen et al., 2017 ) ( Figure 1 D).…”
Section: Resultsmentioning
confidence: 82%
“…Bulk RNA-seq was performed as a service at Novagen after the cells passed quality control. The expression profiles of the RNA-seq data were compared to published reference datasets of iPSC, LCL, and fibroblasts (GEO: GSE79636 , HipSci, GEO: GSE121926 , E-MTAB-4652) ( Carcamo-Orive et al., 2017 ; Kaisers et al., 2017 ; Kilpinen et al., 2017 ; Ozgyin et al., 2019 ) analyzed with the same methods.…”
Section: Methodsmentioning
confidence: 99%
“…Higher depths (typically on the order of ca. 100×) are sometimes used in RNA-seq for identification of splicing events. , Our experiments suggest that of the modifications tested, most would still not be distinguishable at this depth. One exception is m6G, since its miscoding rate is high, but it would likely only be distinguishable at high levels of occupancy.…”
Section: Discussionmentioning
confidence: 83%